The Political Public Relations of Muhammadiyah Leader in the Covid-19 Pandemic Era - Harmonis Harmonis; Diah Febrina (International Journal of Media and Communication Research (IJMCR), 2022)
The purpose of the study on Political Public Relations (PRP) of Muhammadiyah Leaders in the era of the covid-19 pandemic is to find out about the relationship in the political context between the leadership of the Muhammadiyah Branch and the public or stakeholders in their respective branches, especially in the era of the covid-19 pandemic. The concepts used are political public relations and political public relations activities. This study uses qualitative methods with data collection techniques through interviews and document analysis. The results of the study show that although administratively branch leaders have not mapped or recorded data based on modern and professional administrative guidelines and stored in a complete data and documentation center (Pusdatin) about stakeholders, in general branch leaders have understood that those who are stakeholders or those who are interested and who The interests of the Muhammadiyah Branch in East Jakarta are the community around the branch, community leaders or opinion leaders, the sub-district government and political parties and the media. With regard to political public relations activities, the leadership of Muhammadiyah branches throughout East Jakarta varies widely, both internally (relationships within the Muhammadiyah organization, fellow members or fellow administrators), and external (with outside members and administrators). In conclusion, the leadership of Muhammadiyah branches throughout East Jakarta, still really needs to increase data collection and carry out various activities related to political public relations, specifically conducting data collection and activities that are well documented through the data and information center (Pusdatin) in each branch. The benefit is that when there are parties who need information, especially regarding stakeholders and political public relations activities of branch leaders, it can be easily provided to those in need.